UPAYA MENINGKATKAN KEMAMPUAN BERBICARA PADA MATA PELAJARAN BAHASA INGGRIS MELALUI METODE DEMONTRASI SISWA KELAS III SD NEGERI 157 PEKANBARU - Darsiana Darsiana (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research is motivated by low speech ability of third grade students of SD Negeri 157 Pekanbaru. This studyaims to students' speaking ability with the application of class III demontration method SD Negeri 157Pekanbaru. The subjects of this study are all students of class III SDN 157 Pekanbaru which amounted to 33people. The form of research is classroom action research. The instrument of this research consists ofperformance instruments and data collection instruments in the form of observation sheet of teacher activity andstudent activity. Based on the results of research and discussion can be concluded that students' speaking abilitycan be improved. This is evident from the average of students on the initial test obtained an average value of66.97 with a mastery of 15 people (45.45%) and increased in the cycle I to 71.97 with completeness reached 23people (69.70%) . Improved students' speaking ability better again in cycle II is reached at the average value of75.15 with the completeness to reach 30 students (90,91%), thereby the value of student's completeness has beenreached.